Eksploitasi Anak sebagai Tindak Pidana: Analisis Implementasi Penegakan Hukum dalam Sistem Peradilan Pidana Anak - Pesona Bias Pelangi Karina Putri (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
Child exploitation is a serious violation of human rights that involves children as victims. In Indonesia, such cases frequently occur due to severe economic pressure, lack of education, weak social supervision, and inadequate law enforcement. Children are often used as laborers or sources of income, either directly in the informal sector or through digital media. This study aims to examine how the juvenile criminal justice system in Indonesia addresses cases of child exploitation and to evaluate the effectiveness of legal protection for child victims. The research employs a normative juridical approach by referring to statutory regulations and relevant legal concepts. Data were collected from various primary legal sources, including the Child Protection Law and the Juvenile Criminal Justice System Law. The findings indicate that although legal regulations are relatively clear and firm, their implementation in practice remains problematic. Coordination among institutions is not yet effective, social rehabilitation for victims is insufficient, and public awareness regarding children’s rights remains low. Law enforcement also has not fully prioritized the restorative justice approach, which emphasizes victim recovery and active community involvement. Therefore, stronger and more integrated legal policies, improved law enforcement capacity, and the empowerment of families and communities are required to ensure sustainable child protection.